Does your stored maize turn brown? - Technical Centre for Agricultural and Rural Cooperation (Technical Centre for Agricultural and Rural Cooperation, 1995)
Maize stackburn, the discoloration of stored maize as a direct result of heat build-up in the interior of stacks, has emerged as a significant threat to food security in sub-Saharan Africa during the last decade. The problem affects white and yellow...